Concomitant acute ischemic stroke and upper extremity arterial occlusion: feasibility of mechanical thrombectomy of the upper limb using neurointerventional devices and techniques - Vollherbst, Dominik; Ulfert, Christian; Maus, Volker; Boujan, Timan; Henkes, Hans; Bendszus, Martin; Möhlenbruch, Markus Alfred (Journal of Clinical Medicine, 2021)
Background: Concomitant acute ischemic stroke (AIS) caused by large vessel occlusion (LVO), and acute upper extremity arterial occlusion causing upper limb ischemia (ULI) is a rarely observed coincidence. The first-line treatment for AIS is mechanical thrombectomy (MT), with or without additional intravenous thrombolysis, while there are different pharmacological, surgical and endovascular treatment options for an acute occlusion of the UL arteries. Here, we describe the practicability, efficacy and safety of neurointerventional devices and techniques for MT of upper extremity arterial occlusions. Materials and Methods: A retrospective analysis of prospectively collected patient databases from four neurovascular centers was performed. Clinical and imaging data, as well as procedural parameters, were assessed. Results: Seven out of 6138 patients (incidence: 0.11%) presenting with an AIS due to the occlusion of craniocervical arteries requiring MT and a concomitant occlusion of the brachial (4/7), axillary (2/7), or ulnar (1/7) artery causing acute ULI were identified. Craniocervical MT was technically successful in all cases. Subsequent MT of the upper limb was performed using neurointerventional thrombectomy techniques, most frequently stent retriever thrombectomy (in 4/7 cases) and direct aspiration (in 7/7 cases). MT achieved successful recanalization in 6/7 cases, and the UL completely recovered in all six cases. In one case, recanalization was not successful, and the patient still had a marginally threatened extremity after the procedure, which improved after pharmacological therapy. Conclusion: In the rare case of AIS requiring MT and concomitant acute upper extremity arterial occlusion, MT of the UL arteries using neurointerventional devices and techniques is practical, effective, and safe.